PKM Usaha Ekonomi Produktif Kelompok PKK Desa Cepiring Kecamatan Cepiring Kabupaten Kendal - Wyati Saddewisasi; Sri Haryati; D.C. Kuswardani (Khadimul Ummah, 2019)
The member of Family Empowerment for Welfare (PKK) at RT 05 RW 03 Cepiring Village, Cepiring Sub-District, Kendal Regency currently (October 2018) is 20 people. They are conducting productive economic activities on batik, snacks (cookie and pastry), ginger drink, catering, tailoring, grocery and accessories. 60% of the total members are engaging in food field. Semarang University Community service team has conducted PKM (Community Partnership Program) avtivities using funds from the Ministry of Research, Technology and Higher Education, specifically for the food business. The problems faced by the group members such as: production and packaging, finance and marketing. The offered solution is to increase production and good product packaging, to provide assistance tools, to provide understanding on finance field and good marketing. The service methods performed including Evaluating Business Activities, Training and Counselling, Monitoring. Activities evaluation was performed both before implementation fo service to the community, The service result indicated that both quantity and quality of production have increased. As an illustration of this service result, a new oven can increase total production in one process up to 4 (four) times higher than used old oven. Bisides, new tools namely vacuum, sealer and spiners can improve the production quality. Furthermore, the understanding of financial and marketing fields still needs further assistance.